Spellwright - Charlton, Blake (New York : Tor, 2010)
'Nicodemus Weal has trained at the wizardly stronghold of Starhaven since he was a boy. His mentor, the famous wizard Agwu Shannon, taught him how to cast spells made from luminescent magical runes, how to peel written words off a page and make them physically real, how to protect himself with defensive paragraphs, and how to thrust sharply worded sentences at an enemy. Initially, Nicodemus showed great promise. Able to forge magical runes with great speed, he was once thought to be the Halcyon--a powerful spellwright prophesied to prevent the apocalypse known as the Disjunction. There was only one problem: Nicodemus couldn't spell. Every time he touched a magical text, he unintentionally corrupted it, turning a useful spell into a dangerous, potentially deadly misspell. Even now, at twenty-five, Nicodemus's problem remains so bad that he is allowed to use his magic only for janitorial tasks. While his peers advance as wizards, he is still an apprentice, living with other disabled spellwrights and reading knightly romances that fuel his dreams of escape and adventure. When a powerful wizard is murdered with a misspell, Nicodemus and Shannon both are suspected. Worse, Nicodemus dreams of a foreign city under attack from an ancient, godlike spell...and wakes to find Starhaven abuzz with news of that city's actual destruction. A second nightmare makes Nicodemus begin to question his own sanity. When there are more mysterious deaths, the authorities hunt him as a murderer. Tormented and desperate, Nicodemus has no choice but to flee his pursuers so that he can discover the truth about the murders, the nature of magic...and himself.'--Dust cover flap.
Keywords: Wizards -- Fiction; Magic -- Fiction; Murder -- Fiction